To study the effectiveness of self-instructional module on knowledge and selected outcome among women undergoing hysterectomy in a tertiary care hospital in South India - MC, Elgi; Viswanath, Lekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Hysterectomy is a one of the major operations of surgical treatment in Gynecology. The purpose of the study was to assess the effectiveness of Self -Instructional Module (SIM) on knowledge and selected outcome among women undergoing hysterectomy at a tertiary care hospital Kochi. Methods: An experimental approach with a pretest-posttest control group design was used for the study. Forty women posted for hysterectomy were selected by convenience sampling technique. First 20 samples were allotted to experimental group and second 20 to the control group to avoid data contamination. SIM was given to the women in the experimental group after the pretest and post-test of both group was done on the fourth post-operative day. The socio-demographic and clinical data were collected by a semi-structured interview. A semi structured questionnaire was used to assess the pretest and posttest knowledge. The selected outcomes were measured using a ten point visual analogue scale in the fourth postoperative day. Data analysis was done by using descriptive and inferential statistics. Results: The findings of the study revealed that the pre-test level of knowledge among experimental group was average for 13 (65%), and poor for seven (35%), whereas in post-test 12 (60%) subjects had good knowledge and eight (40%) had average knowledge. The mean post-test score of knowledge in the experimental group (19.95 + 3.268) is higher than the mean pre-test score of knowledge (10.80 + 3.847) and the post-test score of control group (9.5+4.2). These differences in the means were significant at P<0.001. The mean score of all the selected outcomes were less in the experimental group than the control group. The difference in mean score was significant at p <0.001 in variable like pain, head ache, abdominal discomfort, insomnia, fatigue, anxiety and at P <0.05 level in variables like pain on surgical site, pain on back, pain on abdomen. Conclusions: Based on the major findings of the study, it was concluded that the self-instructional module on hysterectomy was effective in improving the knowledge of subjects and they felt it more useful in identifying the possible post-operative problems like pain on abdomen, surgical site pain, head ache, abdominal discomfort, insomnia, fatigue and anxiety. And take necessary steps to prevent it. SIM was effective as they could read and clear their doubts at their own place. More over the subjects experienced minimal problems associated with the surgery and subjects verbalized that they felt more comfortable to ask their doubts during the time of post assessment.